Besedotvorje predmetnopomenskih besed v Bohoričevi slovnici Zimske urice proste - Stramljič Breznik, Irena (Slavia Centralis, 2020)
Word formation of meaningful word categories in Bohorič’s grammar Zimske urice proste This article takes into account word-formation of the most typical meaningful word categories in the first Slovene Grammar Book written by Adam Bohorič. It examines his tendency to describe and classify word-formation elements typical and present in spoken and/or written Slovene language of the 16th century, despite his Latin training.